Pendampingan Masyarakat Melalui Pembuatan Media Tanam Hidroponik Dan Polybag Untuk Mewujudkan Keluarga Mandiri Pangan Di Desa Puger Kulon Kabupaten Jember: (Community Assistance Through The Manufacture Of Hydroponic Planting Media And Polybags To Realize Food-Independent Families In Puger Kulon Village, Jember Regency) - Afifah Nur Aini; Lailatul Qomariyah; Ahmad Zubairi; Muhammad Rahid Dhaifullah; Rama Bayu Pangestu; Putri Yunita Lestari; Lilis Kurnia Sari; Fenti Nur Hasanah; Moch Hafido Fahmi; Nailiyatun Najahah; Imam Masudi Alfariqi; Kholisatul Ilmiah; Muhammad Reza Maulana; Abdulloh Imas Alhamdi; Helmi Aulia Abid; Ahmad Hamdan (AL HAYAT: Jurnal Pengabdian Masyarakat, 2024)
Puger Kulon Village has a social asset namely Generasi Muda Gedangan (GMG) as a Youth Organization. One of the activities carried out is hydroponic vegetable planting. The KKN Team of UIN Kiai Haji Achmad Siddiq Jember views this as an asset that can be empowered for family-food independence. This community service activity uses Asset Based Community Development approach with the following stages: (a) define, by mapping village assets in the form of individual, natural resources, religion, culture, social, and physical assets, (b) dream, the expectation of community members to meet the food needs of the family by utilizing the yard of the house, (c) design, by designing activities with GMG in the form of hydroponic vegetable planting and using polybag media,  (d) define, including planting vegetables hydroponically and socializing the method to residents as well as planting vegetables using polybags and distributing the seeds to residents, (e) destiny, it known that residents feel happy to be helped by these activities.